Genomic characterization of antifungal Acinetobacter bacteria isolated from the skin of the frogs Agalychnis callidryas and Craugastor fitzingeri. Issue 12 (26th October 2022) - Cevallos, M A; Basanta, M D; Bello-López, E; Escobedo-Muñoz, A S; González-Serrano, F M; Nemec, A; Romero-Contreras, Y J; Serrano, M; Rebollar, E A
Abstract: Chytridiomycosis, a lethal fungal disease caused by Batrachochytrium dendrobatidis ( Bd ), is responsible for population declines and extinctions of amphibians worldwide. However, not all amphibian species are equally susceptible to the disease; some species persist in Bd enzootic regions with no population reductions. Recently, it has been shown that the amphibian skin microbiome plays a crucial role in the defense against Bd . Numerous bacterial isolates with the capacity to inhibit the growth of Batrachochytrium fungi have been isolated from the skin of amphibians. Here, we characterized eight Acinetobacter bacteria isolated from the frogs Agalychnis callidryas and Craugastor fitzingeri at the genomic level. A total of five isolates belonged to Acinetobacter pittii, Acinetobacter radioresistens, or Acinetobacter modestus, and three were not identified as any of the known species, suggesting they are members of new species. We showed that seven isolates inhibited the growth of Bd and that all eight isolates inhibited the growth of the phytopathogen fungus Botrytis cinerea . Finally, we identified the biosynthetic gene clusters that could be involved in the antifungal activity of these isolates. Our results suggest that the frog skin microbiome includes Acinetobacter isolates that are new to science and have broad antifungal functions, perhaps driven by distinct genetic mechanisms. Abstract : We characterized the genomes and the antifungal capacities of Acinetobacter bacteria isolated from the skin of two tropical frog species.